The Relationship Between Problem Focused Coping and Anxiety Among Medical Student of Yarsi University Class of 2020 During Covid-19 Pandemic Era, and The Review According to Islamic Perspective - Syahrani Salsabila; Kenconoviyati Kenconoviyati; Muhammad Arsyad (Junior Medical Journal, 2022)
Background: Since Covid-19 was designated as a pandemic case by WHO, the Indonesian government has implemented policies aimed at minimizing the spread of the Covid-19 outbreak. This has an impact, one of which is changing face-to-face learning activities to distance learning. This sudden situation gave rise to feelings of anxiety among students and college students. In overcoming this problem, coping strategies can be applied in the form of problem focused coping. In the Islamic view anxiety and problem focused coping are not explained specifically. However, Islam teaches its people how to solve good problems and how to overcome anxiety, one of which is by remembering Allah SWT. Objective: The purpose of this study is to determine the relationship between the problem focused coping and anxiety among medical student of Yarsi university class of 2020 during Covid-19 pandemic era and the review according to Islamic perspective.  Method: This type of research uses analytical observational methods with a cross-sectional approach. This research was conducted among medical student of Yarsi university class of 2020. The data collection technique used is the dissemination of questionnaires through google forms. The data analysis used is bivariate analysis with spearman rank correlation test. Result: Based on the result, the probability and the Rank-Spearman correlation value are p = 0.000 and -0.493, it shows that there is a relationship between problem focused coping and anxiety with negative correlation.  Conclusion: There is a relationship between problem focused coping and anxiety among medical student of Yarsi University class of 2020 during Covid-19 pandemi era.